The Influence of Influencer Marketing, Social Media Marketing, and Electronic Word of Mouth Wom on Skintific Purchase Decisions on Shopee (Case Study in Majalengka Regency) - Dhiany Nurhasanah Hanifa; Fayza Nandika Fitriyani; May Dedu (Riviera Publishing, 2025)
The Indonesian skincare market has evolved with increasing consumer preference for clean, minimalist beauty, leading brands like Skintific to adopt strategic digital marketing approaches. This study aims to analyze the influence of Influencer Marketing, Social Media Marketing, and Electronic Word of Mouth (eWOM) on consumer purchasing decisions, specifically for Skintific products on the Shopee platform in Majalengka Regency. Employing a quantitative approach, data were gathered from 200 respondents via a structured questionnaire and analyzed using multiple linear regression through SPSS Version 27. The findings reveal that all three independent variables significantly influence purchase decisions, with eWOM showing the strongest impact (? = 0.387), followed by Influencer Marketing (? = 0.324), and Social Media Marketing (? = 0.222). The model demonstrated good predictive power, with an R² value of 0.652. These results underscore the importance of digital marketing strategies in shaping consumer behavior and offer actionable insights for businesses to leverage influencer collaboration, social media engagement, and consumer reviews to boost sales. The research contributes to the digital marketing literature by contextualizing consumer behavior in a regional e-commerce setting and highlights the need for future studies to explore moderating variables such as brand loyalty, trust, and demographics to expand generalizability.